PENGARUH LOCUS OF CONTROL DAN PERILAKU KEPEMIMPINAN SITUASIONAL TERHADAP PRESTASI KERJA AUDITOR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Dian Agustia (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
This study aimed to prove the impact locus of control and situational leadership behavior to auditor job performance through job satisfaction. This study uses a quantitative approach that focused on testing the hypothesis. Independent variables are locus of control (LOC), situational leadership behavior (PKS), while the dependent variable are job satisfaction (KK) and job performance (PKA). Data collection procedures in this study was done by a survey using a questionnaire. The respondent was the auditor in accounting firm in East Java. Data analysis techniques to test the research hypotheses are conducted using multiple linear regression analysis. Based on the test, the conclusions obtained are locus of control and situational leadership behavior simultaneously have a significant impact on job satisfaction. Partially, locus of control has no significant influence on job satisfaction but situational leadership behaviors has a significant influence on job satisfaction. Locus of control and situational leadership behavior simultaneously effect significantly on auditor job performance. Partially, locus of control has a significant effect on job performance, but the situational leadership behavior has no significant effect on job performance. Job satisfaction has a significant effect on auditor job performance. The study of locus of control effect on job performance through job satisfaction is not proven. The study proves that there is an indirect effect situational leadership behavior to auditor job performance through job satisfaction as an intervening variable.